REFORMULATION OF STATE PROPERTIES AS A GUIDELINE FOR THE DIRECTION OF INDONESIA'S NATIONAL DEVELOPMENT: REFORMULASI HALUAN NEGARA SEBAGAI PEDOMAN ARAH PEMBANGUNAN NASIONAL INDONESIA - Firna Novi Anggoro (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
Discourse of reviving the direction of the country is still ongoing as an effort to correct the national development planning system that is currently used. The pros and cons of coloring efforts to revive the direction of the country. The revival of the direction of the state is considered a manifestation of the return of the authoritarian system of authoritarianism in the new order era. On the contrary, the positive response to reviving PPHN is able to ensure that national development is more thorough, directed, integrated, sustainable and accountable. The problem is how the urgency of forming PPHN as a guideline for the direction of national development in the future? This research is normative juridical research using a statutory approach (statute approach) and a conceptual approach (conceptual approach). The national development system based on the SPPN Law has various weaknesses. this system is still executive heavy and vulnerable to abuser practices has various weaknesses. this system is still executive heavy and vulnerable to abuse of power. In addition, the current national development system provides a gap between the pattern of government development at the central, provincial, district/city levels plus between the leadership before and after it so as to create development that is directed, sustainable and more accountable. It is necessary to reformulate the PPHN which is regulated in the 1945 Constitution of the Republic of Indonesia and subsequently implemented in the system of administering state government power in Indonesia. The granting of constitutional authority to the MPR in the formation and determination of the PPHN will provide a unified perception considering that all colors of political parties take a common consensus for the interests of the nation and state. The implementation of development will be accountable to the MPR in the form of a performance report, even though the president is no longer the mandate of the MPR. This accountability is an effort to revive the principle of checks and balances on the implementation of national development.